A Celiac Disease Phenotype After Checkpoint Inhibitor Exposure: An Example of Immune Dysregulation After Immunotherapy. Issue 8 (8th August 2019) - Arnouk, Joud; Mathew, Don; Nulton, Ethan; Rachakonda, Vikrant
ABSTRACT: Celiac disease is characterized by duodenal inflammation after exposure to gluten. Checkpoint inhibitors are antibodies that inhibit the inhibitory signals of the cytotoxic T lymphocytes to enhance antitumor responses. A 79-year-old man with an unknown history of celiac disease underwent treatment with pembrolizumab for recurrent left maxillary melanoma. He subsequently developed diarrhea and weight loss. Serology was positive for anti-tissue transglutaminase immunoglobulin A. Upper endoscopy revealed duodenal villous atrophy, which was confirmed on biopsy. A gluten-free diet was not tolerated, and symptoms resolved with withdrawal of pembrolizumab and steroid administration for another medical reason.